Evaluation of method of cohort research articles using Q-coh assessment tool - Babu, Praveena; A., Srividya; T., Suresh (International Journal of Clinical Trials, 2023)
Background: Clinical and evidence-based information is very important in the field of clinical sciences including speech and hearing sciences. More and More professionals are resorting to published articles for knowledge on assessment and intervention that are evidence based. Therefore, there is a need of standard evaluation methods for each type of research that is published. The aim of the study is to investigate the quality of the cohort research articles by using the assessment tool Q-coh and thereby checking the reliability of the assessment tool. Methods: The tool Q-coh developed by Jarde et al with the aim to screen the methodological quality of the primary studies with a cohort design was taken for quality assessment of cohort research articles. Q-Coh consists of 26 items and 7 inferences. Assessment was carried out by few reviewers who were blinded to the classification of quality and based on the evaluation received from the reviewers the quality of the articles were determined. Agreement analysis was done to check the proportion of agreement between the raters and reliability of the tool respectively. Results: The research findings indicate that there is a fair to substantial agreement between the raters. Further, the quality of the articles was determined and classified into the class of acceptable and good quality. Conclusions: The present study was conducted to check if the checklist Q-coh is applicable to assess the methodological quality of cohort research studies. The outcomes of the study indicate that the tool is reliable.